Proceso de atención de enfermería en neonato con enfermedad hemolítica por incompatibilidad del Sistema Rh. - Flores Campuzano, Yadira Pilar (2020)
Hemolytic disease of the newborn is an alloimmune disease common due to the destruction of the fetal red blood cell during fetal and neonatal life as a result of the incompatibility of the maternal-fetal blood group. Jaundice usually manifests during the first 24 hours of life and reveals the highest bilirubin levels between the first and fourth days of. The clinical picture can change, depending on the magnitude of the sensitization, from jaundice or mild anemia, to the most severe form, which is the fetal anasarca. In rare situations, the child may be born asymptomatic and immediately afterwards begin to manifest the symptoms, therefore, when there is a history of this condition, close surveillance and study of the newborn should be maintained. With regard to the behavior of the disease in the newborn, the practice of exchange transfusion and phototherapy remain the most recognized and beneficial therapeutic guidelines. The purpose of this clinical case is to develop the nursing care process in a newborn with Hyperbilirubinemia due to incompatibility of the RH system, said that will allow determining the needs and / or potential health problems that the newborn presents by identifying diagnoses. nursing and the application of nursing care in a comprehensive manner, achieving their speedy recovery and well-being.